BAD DEBTS IN BANKING: MANAGEMENT AND PREVENTION STRATEGIES - Hety Devita; Irsyad Kamal; Lukman Hakim (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This research produced key findings related to the causes, handling, and preventive efforts of non-performing loans. The analysis revealed that the main causative factors are the debtors' inability to manage their finances and economic fluctuations. This inability is often caused by miscalculations or a sudden drop in income, such as a decline in business sales or job loss. Conversely, economic turmoil such as inflation, high interest rates, or recession also exacerbates the situation, making it difficult for debtors to meet payment obligations. Dealing with non-performing loans requires a layered approach that is customized, depending on the specific conditions of the debtor and creditor. One effective method is loan restructuring, which involves modifying the terms and conditions of the loan to make it more affordable for the debtor. In addition, asset seizure and liquidation is also a last resort to reduce losses for creditors. Enforcement of credit risk management through stricter evaluation of creditworthiness and utilization of advanced technology is also important to minimize the risk of future non- performing loans. For the prevention of non-performing loans, continuous financial education and good communication with debtors are essential first steps. Financial education programs can help individuals and businesses understand better financial management, while proactive communication between lenders and borrowers provides early warning of potential financial problems. In addition, the implementation of stricter credit policies and closer monitoring of creditor performance are also important steps in the prevention of non-performing loans before the problem becomes unmanageable. Overall, the handling and prevention of non-performing loans requires good coordination and a comprehensive approach from various relevant parties. Lenders need to develop more sophisticated procedures and tools for risk evaluation and management, while borrowers need to be adequately educated on financial management. With these collective efforts, the risk of non-performing loans can be minimized and financial stability at the micro and macro levels can be better ensured.